2006
DOI: 10.2106/jbjs.e.01280
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Intoeing Gait in Children with Cerebral Palsy

Abstract: More than one-third of children with cerebral palsy have multiple causes of intoeing. Pes varus commonly contributes to intoeing by children with hemiplegic cerebral palsy but rarely contributes to intoeing by those with diplegia or quadriplegia. These findings should be carefully considered prior to surgical correction of the intoeing gait of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…We agree with others (Arnold et al 2000, Rethlefsen et al 2006, Lovejoy et al 2007) that soft tissue surgery should not be recommended to correct pronounced internal rotation, as this is almost universally associated with bony deformity rather than with spastic muscles alone and need rotational osteotomy for adequate correction. Even so, in more moderate rotational deformities and when there is doubt as to whether to perform a large operation including bony surgery, an improvement in rotational deformities can be expected as a side effect following soft tissue procedures aimed at correction of deformities in the sagittal plane.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We agree with others (Arnold et al 2000, Rethlefsen et al 2006, Lovejoy et al 2007) that soft tissue surgery should not be recommended to correct pronounced internal rotation, as this is almost universally associated with bony deformity rather than with spastic muscles alone and need rotational osteotomy for adequate correction. Even so, in more moderate rotational deformities and when there is doubt as to whether to perform a large operation including bony surgery, an improvement in rotational deformities can be expected as a side effect following soft tissue procedures aimed at correction of deformities in the sagittal plane.…”
Section: Discussionsupporting
confidence: 76%
“…Thus in-toeing was considerably more frequent than out-toeing. Rethlefsen et al (2006) found that in-toeing was most often associated with increased internal hip rotation. We found no statistically significant preoperative correlations between foot progression and either hip rotation or pelvic rotation.…”
Section: Discussionmentioning
confidence: 96%
“…Children with in-toeing gait who visited the outpatient clinic of the university hospital were included in this study if they met the following criteria: (1) hip internal rotation ≥60° and trochanteric prominence angle ≥20° [2818], (2) bilateral involvement, (3) age over 8 years, (4) symptoms, frequent tripping and fatigue like pains, (5) symptom duration ≥1 year, and (6) no effect from previous rehabilitation therapy such as gait plate and home stretching programs, received for at least an year prior to participation in this study. For trochanteric prominence angle measurement, children's knees were flexed to 90° in prone position.…”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria were: (1) internal tibial torsion (thigh-foot angle of <0° [825]), (2) metatarsus adductus (adduction of the forefoot without varus was clinically assessed), (3) injury or surgery of the lower limb, (4) serious deformities of the lower limb that would affect gait, and (5) neurodevelopmental disorders, such as cerebral palsy or intellectual disability. For the thigh-foot angle, the angle formed by each line that divides the longitudinal axis of the thigh and calcaneus was measured in prone position with the knees bent 90° and the ankle in the neutral position using goniometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation